Proceso de aceptación en tres familias frente a la discapacidad cognitiva de sus hijos en el municipio de La Unión, Valle - Hernández Aguirre, Eliana María (Universidad Antonio Nariño, 2022)
The purpose of this research is to learn more about the acceptance process of three (3) parents from the municipality of La Unión, Valle. In order to obtain this information, a qualitative methodology was implemented with a phenomenological method. A semi-structured interview, and the genogram were used as instruments. These instruments were applied to three (3) parents, in order to learn more about the family history, its dynamics and structure.